Peran Komisi Perlindungan Dan Pengawasan Anak Daerah Provinsi Kalimantan Barat Dalam Penanganan Kekerasan Seksual Pada Anak Tahun 2021 - diana, Mar; Jannah, Nur; Irfani, Amalia (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2021)
Abstract: This paper aims to discuss the efforts of the West Kalimantan Regional Child Protection Commission in dealing with sexual violence against minors. The method used in collecting data in writing this article is a combination of field study methods with literature studies. Sexual violence is an act that is intentional and can harm victims who are children, both physically and psychologically. The role of the West Kalimantan Regional Child Protection and Supervision Commission is very much needed in handling cases of minors, especially on the issue of sexual crimes. Furthermore, parents should also be involved in handling minimal sexual violence by teaching children to recognize, refuse, and report potential threats of sexual violence if it occurs to them. Finally, parents should also have good emotional attachment and also support children legally if sexual violence occurs so that the perpetrators of sexual violence roaming the community can be punished accordingly for their behavior.